2022
DOI: 10.1002/trc2.12262
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of cognitive training and brain stimulation in non‐demented older adults

Abstract: Introduction Given rapid global population aging, developing interventions against age‐associated cognitive decline is an important medical and societal goal. We evaluated a cognitive training protocol combined with transcranial direct current stimulation (tDCS) on trained and non‐trained functions in non‐demented older adults. Methods Fifty‐six older adults (65–80 years) were randomly assigned to one of two interventional groups, using age and baseline performance as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 47 publications
(152 reference statements)
2
44
0
1
Order By: Relevance
“…Corroborating and extending these and previous ndings, we here showed that the functional coupling between bilateral prefrontal regions -part of the frontoparietal network -was increased through tDCS, suggesting that enhanced temporal coherence of BOLD activity is one of the mechanisms underlying tDCS effects. By enabling more coordinated/synchronized activity between network hubs, tDCS combined with repeated sessions may produce (potentially longer-term) transfer effects 2,15,25,50 . In our data, we did not observe an association between FC changes and behavioral performance gains, pointing to a rather complex relationship which may also be masked by the impact of baseline FC on behavioral modulation 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corroborating and extending these and previous ndings, we here showed that the functional coupling between bilateral prefrontal regions -part of the frontoparietal network -was increased through tDCS, suggesting that enhanced temporal coherence of BOLD activity is one of the mechanisms underlying tDCS effects. By enabling more coordinated/synchronized activity between network hubs, tDCS combined with repeated sessions may produce (potentially longer-term) transfer effects 2,15,25,50 . In our data, we did not observe an association between FC changes and behavioral performance gains, pointing to a rather complex relationship which may also be masked by the impact of baseline FC on behavioral modulation 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…All participants were right-handed, native German speakers, had no history of neurological or severe psychiatric diseases, did not take any central nervous system active medication, and performed within age-and education-adjusted normative range in the neuropsychological screening (Consortium to Establish a Registry for Alzheimer's Disease, CERAD-Plus Test Battery, https://www.memoryclinic.ch). All participants completed the TrainStim-Cog clinical study where they received anodal or sham transcranial direct current stimulation over the left prefrontal cortex during three weeks (totaling up to nine sessions) of a training of two executive functions tasks (a letter updating task and a value-based Markov decision making task 25,26 , NCT03838211, https://clinicaltrials.gov/show/NCT03838211). All behavioral data is reported in 25 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cognitive training study with a group of elderly participants did not show an expected effect of tDCS on task performance when applying a protocol with 1 mA current intensity, derived from studies with young participants (Antonenko et al, 2022). The authors indicate signs of atrophy in their retrospectively analyzed head models for current flow modeling and indicated the missing correction for effective electric field strength as a compromising factor on the stimulation results.…”
Section: Induced Field and Stimulation Montage Based On Individual Mo...mentioning
confidence: 95%
“…Similar to the use of NIBS to boost neuropsychological rehabilitation after disruption of function due to stroke, these techniques might have the potential to support preservation of cognitive functions in pathological but also healthy aging through modulation of cortical excitability and the enhancement of neuroplasticity (Hartwigsen, 2018, 2015; Siebner et al, 2009). While there are some first promising results from different cognitive domains (for reviews, see Booth et al, 2022; Goldthorpe et al, 2020; Hsu et al, 2015), particularly when NIBS is coupled with training interventions, variability remains high and some studies find no beneficial effect of stimulation (e.g., Antonenko et al, 2022). Further insight into the potential of NIBS in aging can be gained by investigating the effect of stimulation on neural activity and functional connectivity.…”
Section: Introductionmentioning
confidence: 99%